=
Note: Conversion is based on the latest values and formulas.
How do you evaluate #sin (pi/2)#? - Socratic 15 Aug 2016 · If in a right angled triangle #theta# represents one of its acute angle then by definition we can write. #color(red)(sintheta="Opposite"/"Hypotenuse")#
How do you solve and find the value of #sin^-1(pi/2)#? - Socratic 23 Jul 2017 · pi/2=1.570796... and is greater than one and as sine of any angle can only take values in the interval [-1,1], there is no solution.
What is sin(2pi/3) equal to? - Socratic 9 Mar 2018 · color(green)(sqrt3 / 2) sin ((2pi) / 3) = sin (pi - ((2pi)/3) )= sin ((3pi - 2pi) / 3) = sin (pi)/3 sin ((pi)/3) = sin 60 = sqrt3 / 2
How do you find sin(-pi/2)? - Socratic 4 May 2018 · #"using the "color(blue)"trigonometric identity"# #•color(white)(x)sin(-x)=-sin(x)# #rArrsin(-pi/2)=-sin(pi/2)=-1#
What is #sin(x+pi/2)#? - Socratic 16 Apr 2015 · cos x With pi/2 add to any angle measure, sin changes to cos and vice- versa. Hence It would change to cosine and since the angle measure falls in the second quadrant, …
How do you verify the identity sin(pi/2 + x) = cosx? | Socratic 23 Apr 2015 · for the "true" proof you need to use matrice, but this is acceptable : sin(a+b) = sin(a)cos(b)+cos(a)sin(b) sin(pi/2+x) = sin(pi/2)*cos(x)+cos(pi/2)*sin(x) sin(pi/2) = 1 cos(pi/2) = …
How do you simplify #sin(x-pi/2)#? - Socratic 16 Aug 2016 · The answer given prior is a perfectly valid explanation, but here is another: We must consider our knowledge of transformations:
How do you graph # y= sin (pi/2) x#? - Socratic 2 Apr 2016 · Note that sin(pi/2) = 1. Therefore, y = sin(pi/2) * x = x Below is a graph of y = sin(pi/2) * x graph{x [-10, 10, -5, 5]}
How to prove that #sin (pi/2 - theta)# = #cos theta# - Socratic 13 Mar 2016 · using appropriate #color(blue)" Addition formula " # #• sin(A ± B) = sinAcosB ± cosAsinB # hence # sin(pi/2 -theta) = sin(pi/2) costheta - cos(pi/2)sintheta #
How do you evaluate #1/2 (sin (pi/2) + sin (pi/6))#? - Socratic 15 May 2016 · 3/4 Call the product P = (1/2)p Apply the trig identity: sin a + sin b = 2sin ((a + b)/2).cos ((a - b)/2). We get: sin ((a + b)/2) --> sin ((pi/2+ pi/6)/2) = sin (pi ...